Postnatal Cytomegalovirus Exposure in Infants of Antiretroviral-Treated and Untreated HIV-Infected Mothers. (2nd March 2014) - Meyer, Sarah A.; Westreich, Daniel J.; Patel, Emily; Ehlinger, Elizabeth P.; Kalilani, Linda; Lovingood, Rachel V.; Denny, Thomas N.; Swamy, Geeta K.; Permar, Sallie R.
Abstract : HIV-1 and CMV are important pathogens transmitted via breastfeeding. Furthermore, perinatal CMV transmission may impact growth and disease progression in HIV-exposed infants. Although maternal antiretroviral therapy reduces milk HIV-1 RNA load and postnatal transmission, its impact on milk CMV load is unclear. We examined the relationship between milk CMV and HIV-1 load (4–6 weeks postpartum) and the impact of antiretroviral treatment in 69 HIV-infected, lactating Malawian women and assessed the relationship between milk CMV load and postnatal growth in HIV-exposed, breastfed infants through six months of age. Despite an association between milk HIV-1 RNA and CMV DNA load (0.39 log10 rise CMV load per log10 rise HIV-1 RNA load, 95% CI 0.13–0.66), milk CMV load was similar in antiretroviral-treated and untreated women. Higher milk CMV load was associated with lower length-for-age (−0.53, 95% CI: −0.96, −0.10) and weight-for-age (−0.40, 95% CI: −0.67, −0.13) Z -score at six months in exposed, uninfected infants. As the impact of maternal antiretroviral therapy on the magnitude of postnatal CMV exposure may be limited, our findings of an inverse relationship between infant growth and milk CMV load highlight the importance of defining the role of perinatal CMV exposure on growth faltering of HIV-exposed infants.